2018
DOI: 10.1038/emm.2017.281
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TNFα-interacting protein α (Tipα)-associated gastric carcinogenesis by BTG2/TIS21 via downregulating cytoplasmic nucleolin expression

Abstract: To understand the regulation of Helicobacter pylori (H. pylori)-associated gastric carcinogenesis, we examined the effect of B-cell translocation gene 2 (BTG2) expression on the biological activity of Tipα, an oncoprotein secreted from H. pylori. BTG2, the human ortholog of mouse TIS21 (BTG2/TIS21), has been reported to be a primary response gene that is transiently expressed in response to various stimulations. Here, we report that BTG2 is constitutively expressed in the mucous epithelium and parietal cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Suganuma et al showed that H. pylori infection increases the quantity of Tipα protein in gastric cancer tissue, inducing tumor progression in H. pylori carcinogenesis [161]. Tipα reduces cell stiffness and phosphorylates various oncoproteins; it also enhances filopodia formation, morphological, and Cells 2020, 9, 1055 5 of 28 conformational changes within cells, and expression of vimentin via MEK-ERK phosphorylation, confirming its role in EMT progression [179,180].…”
Section: Tumor Necrosis Factor α-Inducing Protein Of H Pylori In Emtmentioning
confidence: 94%
“…Suganuma et al showed that H. pylori infection increases the quantity of Tipα protein in gastric cancer tissue, inducing tumor progression in H. pylori carcinogenesis [161]. Tipα reduces cell stiffness and phosphorylates various oncoproteins; it also enhances filopodia formation, morphological, and Cells 2020, 9, 1055 5 of 28 conformational changes within cells, and expression of vimentin via MEK-ERK phosphorylation, confirming its role in EMT progression [179,180].…”
Section: Tumor Necrosis Factor α-Inducing Protein Of H Pylori In Emtmentioning
confidence: 94%
“…Lung sections were incubated with 3% H 2 O 2 for 10 min and then subjected to antigen retrieval using pressure cooking in antigen-activating solution (pH 9, 98 °C). After blocking with Protein Block (Dako, Carpinteria, CA, USA) for 5 min at room temperature, the sections were immunostained with anti–PD-L1 antibody (1:200) for 40 min at 37 °C, followed by secondary antibody (N-Histofine Simple Stain MAX-PO (Multi), Nichirei Bioscience Inc., Tokyo, Japan) for 20 min at 37 °C, as described previously [ 31 ]. Cells showing positive for PD-L1 on the plasma membrane were independently counted by 3 investigators.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue arrays were incubated with anti-SET antibody (1:800) for 40 min at 37°C after blocking with Protein Block (DAKO, Tokyo, Japan), and the secondary antibody (N-Histofine simple stain MAX-PO (Multi), Nichirei Bioscience Inc. Tokyo, Japan) was applied as described previously. 37 The relative staining intensity of SET in breast tissues was reviewed by two independent individuals. The score was calculated based on the staining intensity as percentage of stained cells × intensity score.…”
Section: Methodsmentioning
confidence: 99%